Proceedings of the Third International Conference on Railway Technology: Research, Development and Maintenance
DOI: 10.4203/ccp.110.63
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Factors Affecting Flange-Climb Derailment in Railway Vehicles

Abstract: Avoiding flange climb derailment is one main issue with ensuring the running safety of railway vehicles. This paper discusses the different causes that can lead to the derailment of a railway wheel, particularly in the light of different derailment criteria used by the standards or proposed by various researchers.Furthermore the paper presents two case studies, one for a vehicle with solid axles and one for a bogie with independently rotating wheels, reporting a description of the derailment case and discussin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…The short straight lines or sharp curves are inevitably set before the turnouts with small crossing angles. It was found that sharp curves tend to produce large Y/Q values on the flanging wheel in Diana et al., 26 as a result, this may cause the wheel flange to contact the rail gauge corner before leading wheelset enters the switch panel. Therefore, this section analysed the influence of the curve radius and the length of straight lines before turnouts on the passing performance.…”
Section: Simulation Of Passing Performancementioning
confidence: 99%
“…The short straight lines or sharp curves are inevitably set before the turnouts with small crossing angles. It was found that sharp curves tend to produce large Y/Q values on the flanging wheel in Diana et al., 26 as a result, this may cause the wheel flange to contact the rail gauge corner before leading wheelset enters the switch panel. Therefore, this section analysed the influence of the curve radius and the length of straight lines before turnouts on the passing performance.…”
Section: Simulation Of Passing Performancementioning
confidence: 99%